PRAGMATICS IN LANGUAGE LEARNING: TEACHING CONVERSATIONAL IMLICATURE IN ENGLISH - Mamirova M. M. (Modern American Journals, 2025)
Pragmatics is a subfield of linguistics that focuses on the study of how speakers use language to convey meaning beyond the literal interpretation of words. It examines the context in which language is used, the speaker’s intentions, and the listener’s inferences. Pragmatics is concerned with the study of conversational implicatures, presuppositions, speech acts, and other aspects of language use that go beyond the literal meaning of words.The theory of pragmatics in languages is an important area of study that helps us understand how language is used in social interactions. It has applications in various fields such as education, psychology, and communication studies. By studying pragmatics, we can gain insights into how people use language to convey meaning, how they interpret meaning, and how they make inferences based on contextual cues.
Keywords: Pragmatics, culture of the country, inner meanings of words, crosscultural, principles of politeness.